Dampak Program Pembelajaran Daring di SD Muhammadiyah I Borobudur pada Masa Pandemi : Prestasi Belajar - Sari, Hani Fitria (Prosiding University Research Colloquium, 2021)
This study aims to find out how the teacher’s efforts to improve student achievement during the pandemic. Because during a pandemic like this, learning activities take place differently than usual, namely through online learning that utilizes gadget technology. While learning usually takes place offline or face to face. The research method used is descriptive qualitative research method. Data collection techniques using observation and interviews. From the results of the study, it can be seen that the efforts made by the teacher are good, but there are several factors that become problems for students and are constrained by other things. This study aims to determine the impact of online learning in the context of student achievement.